2021
DOI: 10.1029/2021jg006277
|View full text |Cite
|
Sign up to set email alerts
|

Winter Climate and Lake Morphology Control Ice Phenology and Under‐Ice Temperature and Oxygen Regimes in Mountain Lakes

Abstract: Ice cover is decreasing in many of the world's lakes (Sharma et al., 2019), creating an urgent need to understand drivers of ice phenology and winter ecology in a diversity of lake types (Hampton et al., 2017;Warne et al., 2020). Ice cover duration and timing affect ecosystem functions during open water seasons, such as thermal and mixing regimes (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 64 publications
4
14
0
Order By: Relevance
“…The high elevation lakes that R. sierrae inhabit are under ice and snow cover from approximately November to June. More severe winters lead to longer ice and snow cover, shorter ice‐free durations during summer months and cooler summer water temperatures (Smits et al, 2021). A well‐supported measure/proxy of winter severity is the snow water equivalent (SWE) on April 1st of the current year (extracted from the California Data Exchange Center for snow survey locations across the Sierra Nevada).…”
Section: Methodsmentioning
confidence: 99%
“…The high elevation lakes that R. sierrae inhabit are under ice and snow cover from approximately November to June. More severe winters lead to longer ice and snow cover, shorter ice‐free durations during summer months and cooler summer water temperatures (Smits et al, 2021). A well‐supported measure/proxy of winter severity is the snow water equivalent (SWE) on April 1st of the current year (extracted from the California Data Exchange Center for snow survey locations across the Sierra Nevada).…”
Section: Methodsmentioning
confidence: 99%
“…Using temperature and DO probes in lakes of the Sierra Nevada and the Klamath mountains, Smits et al. (2021) concluded that air temperature and precipitation (snowfall) were the most important drivers of the timing of ice formation and ice‐off, while lake morphometry was the most important factor determining DO depletion rates under ice. They found that seasonal and interannual variability were higher in small, shallow lakes than larger, deeper lakes.…”
Section: Physical and Biogeochemical Dynamicsmentioning
confidence: 99%
“…Cross-lake variation in the ice-off date involved relationships between lake size, snow thickness, and ice thickness. Smits et al (2021) used a set of 15 lakes spanning a large elevation gradient in the Sierra Nevada of California to highlight the considerable among-year variability in duration of ice cover, with about a 40 day difference in duration of ice-cover resulting from variation in winter snowpack and temperature. Very high snowpack on high elevation mountain lakes was identified as a more important driver of ice-off and ice-phenology than in low elevation lakes.…”
Section: Changes In Lake and River Icementioning
confidence: 99%
“…Functioning indicators present some advantages over structural ecosystem components since change in ecosystem process rates can be immediately linked to certain levels of environmental change (Palmer and Ruhi, 2019). For instance, the proliferation of reliable and relatively inexpensive sensors for monitoring dissolved oxygen, and easy-to-use software for the calculation of gross primary production (GPP) and Ecosystem Respiration (ER; Engel et al 2019) is underpinning a revolution in the use of this kind of indicator (Bernhardt et al 2018;Smits et al 2021). These two factors enable scientists to estimate ecosystem metabolism more frequently and in greater detail.…”
Section: The Spanish Mountain National Parksmentioning
confidence: 99%